2020
DOI: 10.1039/c9cc09597g
|View full text |Cite
|
Sign up to set email alerts
|

Interface passivation to overcome shunting in semiconductor–catalyst junctions

Abstract: Mesoporous hematite photoanodes modified with a conductive water oxidation catalyst for photoelectrochemical water oxidation suffer from shunting which is alleviated via selective electrodeposition of the polymer PPO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…The porous nature of the films, beneficial for catalysis, can also bring some drawbacks that are associated with shunting recombination in the area where the substrate is in contact with the electrolyte. To avoid this problem, the addition of an isolating underlayer of a few nanometers-such as Ga 2 O 3 [157], TiO 2 [158], SnO 2 [159], or even the deposition of a top polymeric layer [61]-has been successfully explored. Our group's latest work incorporated the underlayer approach to the improved PP methodology [160].…”
Section: Polymeric-precursor Solution-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The porous nature of the films, beneficial for catalysis, can also bring some drawbacks that are associated with shunting recombination in the area where the substrate is in contact with the electrolyte. To avoid this problem, the addition of an isolating underlayer of a few nanometers-such as Ga 2 O 3 [157], TiO 2 [158], SnO 2 [159], or even the deposition of a top polymeric layer [61]-has been successfully explored. Our group's latest work incorporated the underlayer approach to the improved PP methodology [160].…”
Section: Polymeric-precursor Solution-based Methodsmentioning
confidence: 99%
“…For instance, nanostructuring [45][46][47], surface modifiers [48][49][50], and dopant addition [51][52][53], among others, have been reported and reviewed in the literature to derive synergic approaches capable of increasing the photocurrent benchmarks closer to the theoretical values, and to accomplish the industry-required STH efficiency. Moreover, various fabrication methods have also been developed for increasing this benchmark, including pulsed laser deposition (PLD) [54,55], reactive sputtering [56][57][58], chemical vapor deposition (CVD) [59,60], electrodeposition [61][62][63][64], solvothermal [65][66][67], hydrothermal [68][69][70][71][72], and sol-gel-based approaches [73][74][75][76]. From a simple search in the Scopus (Elsevier) database, displayed in Figure 2, it can be seen that hydrothermal and sol-gel synthesis is involved in ~80% of the reports, whereas others only represent ~20%.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods to avoid shunting include adding intermediate insulating layers and insulating OECs. [ 73,74 ]…”
Section: Performance Of Oec‐decorated Photoanodes: Dependent Factorsmentioning
confidence: 99%
“…Figure 12 has clearly shown that a porous substrate exposing the current collector to the electrolyte will lead to shunting. One way to prevent this is to coat the current collector with a thin compact layer of the SC itself or an insulating layer, e.g., poly(phenylene oxide), [ 74 ] before constructing a more elaborate three‐dimensional architecture to either maximize light absorption or minimize hole diffusion distances. Most of currently available reports focus on how the OEC impact the SC, but more innovative experimental ideas are desperately needed to unravel the opposite side of the mutual relationship.…”
Section: Performance Of Oec‐decorated Photoanodes: Dependent Factorsmentioning
confidence: 99%
“…In this work, we provide new insight into the charge-carrier dynamics at the CuWO 4 /electrocatalyst interface using DWE photoelectrochemistry. Ni 0.75 Fe 0.25 O y (Ni75) was chosen as a model electrocatalyst to probe the interface due to the high electrocatalytic activity for the water oxidation reaction. , CuWO 4 and Ni75 films were prepared via atomic layer deposition (ALD) and photochemical metal-organic deposition (PMOD), respectively. , Prior to catalyst deposition, CuWO 4 photoanodes were modified with poly­(phenylene oxide) (PPO) to eliminate shunting . By directly measuring the potential and the current flowing through the electrocatalyst layer, we reveal that the lack of efficiency improvement for water oxidation is due to inefficient transfer of the photogenerated holes to the electrocatalyst overlayer.…”
Section: Introductionmentioning
confidence: 99%